Non linear vibration analysis of liquid storage tank (University of Thi-Qar Journal for Engineering Sciences, 2014)
This study presents an idealization scheme for the analysis of rectangular storage tanks acted upon by earthquake excitations. Above and below ground tank, are considered. A linear three-dimensional finite element analysis is adopted to predict the natural frequencies. The analysis parameters are the ratio of height to length of the tank, the type of soil, level of water in the tank, and also the wall thickness.Tanks made from steel as well as from concrete are investigated. A general purpose finite element program (ANSYS 12.0)used to model the analysed system. The tank base and wall are modelled by plane strain shell elements. The contained liquid is represented by a special solid element. Finally, the soil is modelled by simple spring-damper elements. The soil medium is idealized by the elastic half space model, that is, linear springs are assumed to represent the structure-soil interface. Which is then modelled by two-node spring dashpot elements.Forced vibration analysis is conducted on above ground and buried concrete tank. This analysis is carried out by applying the records of the North-South component of the 1940 El Centro earthquake with peak acceleration of 0.32g. It is found that the bending stresses in above ground concrete tank is (74.167) % greater than the stresses in buried tank with the same dimensions.